The African swine fever isolate ASFV-Kenya-IX-1033 is highly virulent and stable after propagation in the wild boar cell line WSL - Hemmink, Johanneke D.; Abkallo, Hussein M.; Henson, Sonal P.; Khazalwa, Emmanuel M.; Oduor, Bernard; Lacasta, Anna; Okoth, Edward A.; Riitho, Victor; Fuchs, W.; Bishop, Richard P.; Steinaa, Lucilla (MDPI, 2022)
We describe the characterization of an African swine fever genotype IX virus (ASFV-Kenya-IX-1033), which was isolated from a domestic pig in western Kenya during a reported outbreak. This includes the efficiency of virus replication and in vivo virulence, together with genome stability and virulence, following passage in blood macrophages and in a wild boar lung cell line (WSL). The ASFV-Kenya-IX-1033 stock retained its ability to replicate in primary macrophages and retained virulence in vivo, following more than 20 passages in a WSL. At the whole genome level, a few single-nucleotide differences were observed between the macrophage and WSL-propagated viruses. Thus, we propose that the WSL is suitable for the production of live-attenuated ASFV vaccine candidates based on the modification of this wild-type isolate. The genome sequences for ASFV-Kenya-IX-1033 propagated in macrophages and in WSL cells were submitted to GenBank, and a challenge model based on the isolate was developed. This will aid the development of vaccines against the genotype IX ASFV circulating in eastern and central Africa.